Alleviating defects in perovskites using single-walled carbon nanotubes. (1st October 2022) - Choi, Jin-Myung; Han, Jiye; Rane, Tushar; Kim, Soyeon; Kim, Ick Soo; Jeon, Il
Abstract: Single-walled carbon nanotubes (SWCNTs) are representative one-dimensional materials that show exceptional optical and electronic properties with various tuneable bandgaps. SWCNTs can be integrated into a variety of photovoltaics particularly, perovskite solar cells (PSCs) based on a high level of functionality and purity. In this topical review, we discuss the fundamentals of SWCNTs applied to PSCs as an electron-transporting layer, hole-transporting layer, photoactive layer, and interfacial materials from the literature. Firstly, SWCNTs in PSCs and their defect control properties improving the devices are discussed. Subsequently, electrical and morphological improvement of semiconducting SWCNT added PSCs and other types of CNTs used in PSCs are discussed chronologically. The review and discussion layout the strategies of incorporating SWCNTs within the design frame of next-generation PSCs towards the improvement of the device performance via defect passivation.